2015
DOI: 10.1016/j.jchf.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Photoplethysmographic Signal to Screen Sleep-Disordered Breathing in Hospitalized Heart Failure Patients

Abstract: Screening hospitalized patients with heart failure using targeted inpatient ODI identifies a cohort of patients with a high prevalence of SDB. Our screening strategy provides a potentially cost-effective method for early detection and treatment of SDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, a low-cost screening protocol was effectively able to detect underlying SDB. 8 We showed that the oxygen desaturation index (ODI) as determined by high-resolution photoplethysmography can reliably detect SDB; there was a high concordance with the outpatient apnea-hypopnea index (AHI) as determined by polysomnography.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, a low-cost screening protocol was effectively able to detect underlying SDB. 8 We showed that the oxygen desaturation index (ODI) as determined by high-resolution photoplethysmography can reliably detect SDB; there was a high concordance with the outpatient apnea-hypopnea index (AHI) as determined by polysomnography.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, a low-cost screening protocol was effectively able to detect underlying SDB. 8 We showed that the oxygen desaturation index (ODI) as determined by high-resolution photoplethysmography can reliably detect SDB; there was a high concordance with the outpatient apnea-hypopnea index (AHI) as determined by polysomnography.8 Recent data also suggest that early detection and initiation of therapy for SDB in hospitalized patients may reduce readmissions in patients with congestive heart failure (CHF). patients with SDB on positive airway pressure therapy (PAP) in the outpatient setting ranges from 29% to 84%.…”
mentioning
confidence: 99%
“…Of 5062 patients included in the final database, 1161 patients have been included in prior publications. 9,11,12,16,17 The Thomas Jefferson University Institutional Review Board approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…As noted in the figure, the ratio of direct consults as opposed to screen prompted consults significantly improved over time. The highresolution Plethysmography (HRPO) however, may be a game changer in implementing a cost effective strategy for effective screening of SDB in CHF patients [12].…”
Section: Editorialmentioning
confidence: 99%